Disability employment support services: a case study on transition to formal employment for persons with disabilities in South Africa - Mogensen, Karina Fischer (Department of Medicine, 2022)
General unemployment rates are high in South Africa, but unemployment rates for persons with disabilities in the open labour market are still considerably higher than those of able-bodied persons. Research has identified a number of barriers which hinder the full inclusion of persons with disabilities in the open labour market. These barriers include poor quality education and health care, lack of sufficient accessible infrastructure and information, lack of appropriate knowledge of and access to reasonable accommodation, and attitudinal barriers in society including a narrow belief that equates disability with inability to work. On top of these barriers black persons with disabilities are further marginalised due to the historical intersectional influences of race, poverty and disability in South Africa. With a label of ‘non-productive' and dependent, persons with disabilities struggle to access the open labour market, and sustainable decent formal employment is not a reality for many persons with disabilities. Falling into the category of ‘non-productive' and dependent in a capitalist labour market excludes people not only from getting an income but also from other aspects of well-being such as active participation in one's community, and it denies people the opportunity to realise their basic human rights and human dignity. Disability Employment Support Services (DESS) provide specific supports to facilitate the employment of persons with disabilities but there is little formal knowledge in this area. Through a qualitative case study, I sought to understand why South Africa is still struggling to make real advancements for persons with disabilities in formal employment. The research question was: How are DESS provided by a disability NGO facilitating transition into formal employment for persons with disabilities in South Africa? The study included the main stakeholders as study participants, namely learners with disabilities, the DESS provider, and host employers of the DESS learners. The study site was a disability NGO in the Western Cape Province in South Africa providing DESS.